A Review on the Progressive Collapse Analysis of Reinforced Concrete Frame Structures. Issue 1 (July 2021) - Kumar, Pawan; Lavendra, Samrat; Raghavendra, T
Abstract: The progressive collapse analysis of a reinforced concrete (RC) building occurs when an extreme event arises (vehicle collision, gas explosion, bomb blasts, etc.), which often cause damage to the RC structural frame were a sudden loss of primary structural element takes place or due to the failure of one or more critical structural element leading the structure to partial or entire collapse. The fear of progressive collapse is growing, due to the partial collapse of the 22-story Ronan point apartment in 1968, leading to a gas burst and attacks in Oklahoma City, the Alfred P. Murrah Federal Building in 1995, and the attacks on the world trade center in Lower Manhattan, New York in the year 2001. The trend is now to attain strong buildings which can be operational after such extreme events, especially when the building is occupied by a large number of persons. This paper reviews the progressive collapse study on RC frame structure based on various numerical, analytical, and experimental methods which are reported and discussed in the literature. In comparison with bare RC frame, the advantageous impact of the masonry infill wall on the RC structural frame is summed up against the progressive collapse.